2010
DOI: 10.1111/j.1755-3768.2010.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Lens opacity and refractive influences on the measurement of retinal vascular fractal dimension

Abstract: ABSTRACT.Purpose: To examine the influence of lens opacity and refraction on the measurement of retinal vascular fractal dimension (Df). Methods: Optic disc photographs (right eyes) of 3654 baseline Blue Mountains Eye Study participants (aged 49-97 ) were digitized. Retinal vascular Df was quantified using a computer-based program. Summated severity scores for nuclear, cortical and posterior subcapsular (PSC) cataract were assessed from lens photographs. Refraction data were converted to spherical equivalent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 30 publications
(82 reference statements)
4
40
0
Order By: Relevance
“…Based on fundus images, a reduction in the large retinal vessel density was associated with myopia. 6,19 However, Chueng et al 22 found no difference between myopic and normal eyes after correcting for field of view magnification. Hollo et al, 23 using the Heidelberg retina flowmeter, reported that capillary perfusion near the temporal edge of the optic disc was significantly decreased in healthy subjects and glaucoma patients with myopia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on fundus images, a reduction in the large retinal vessel density was associated with myopia. 6,19 However, Chueng et al 22 found no difference between myopic and normal eyes after correcting for field of view magnification. Hollo et al, 23 using the Heidelberg retina flowmeter, reported that capillary perfusion near the temporal edge of the optic disc was significantly decreased in healthy subjects and glaucoma patients with myopia.…”
Section: Discussionmentioning
confidence: 99%
“…6,19 Indeed, OCTA revealed alterations in both the superficial and deep retinal vascular plexuses, which indicates that alterations occur throughout the entire retina. Considering that the degree of decreased microvascular density correlated with axial elongation, the significantly altered microvascular network in highly myopic eyes may represent disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…114 Other ocular factors, including retinal pigmentation, pupil dilation, presence of cataract, and other ocular media opacities, may vary image brightness, focus, and contrast, which significantly affect the measurement of retinal vascular changes. [115][116][117] Furthermore, photographic technique and camera type may also affect the image quality for retinal fundus photography. Such possible ocular factors and confounders should be controlled for (eg, factoring in magnification effect and iris color) in the further development of retinal vascular imaging technology.…”
Section: What Are Technological Challenges In Retinal Vascular Imaging?mentioning
confidence: 99%